MDH: A High Speed Multi-phase Dynamic Hash String Matching Algorithm for Large-Scale Pattern Set - Zhou, Zongwei; Xue, Yibo; Liu, Junda; Zhang, Wei; Li, Jun (Information and Communications Security, 2007)
String matching algorithm is one of the key technologies in numerous network security applications and systems. Nowadays, the increasing network bandwidth and pattern set size both calls for high speed string matching algorithm for large-scale pattern set. This paper proposes a novel algorithm called Multi-phase Dynamic Hash (MDH), which cut down the memory requirement by multi-phase hash and explore valuable pattern set information to speed up searching procedure by dynamic-cut heuristics. The experimental results demonstrate that MDH can improve matching performance by 100% to 300% comparing with other popular algorithms, whereas the memory requirement stays in a comparatively low level.